COI-based diversity of mahseer (Tor spp.) reveals divergent lineages across four foothill rivers of Mount Slamet, Central Java, Indonesia - SUWARSITO SUWARSITO; IKHSAN PRATAMA; HINDAYATI MUSTAFIDAH (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Suwarsito, Pratama I, Mustafidah H. 2026. COI-based diversity of Mahseer (Tor spp.) reveals divergent lineages across four foothill rivers of Mount Slamet, Central Java, Indonesia. Biodiversitas 27 (5): d270505. https://doi.org/10.13057/biodiv/d270505. DNA barcoding has become an essential tool for resolving taxonomic ambiguity in freshwater fishes, including the economically and ecologically important mahseer (Tor spp.). This study employed mitochondrial Cytochrome C Oxidase subunit I (COI) barcodes (~700 bp) to identify species, assess genetic diversity, and infer phylogenetic relationships among 14 individuals collected from four upstream rivers at the foothills of Mount Slamet, Indonesia (Comal, Welo, Tutung Gunung, and Pelus rivers). Basic Local Alignment Search Tool (BLAST) and Barcode of Life Data System (BOLD) analyses assigned sequences to Tor tambroides (99.68% to 99.84% similarity) and Tor tambra (100% similarity). Analysis of Kimura 2-Parameter (K2P) genetic distances by species revealed extremely low intraspecific divergence within T. tambroides (0.0000-0.0035) and generally low divergence within T. tambra (0.0000-0.0266). In contrast, interspecific divergence between T. tambroides and T. tambra ranged from 0.0285 to 0.0303, forming a clear barcode gap. Maximum likelihood phylogenetic analysis placed all samples within the Southeast Asian Tor clade, with clustering concordant with species-level identification. However, given the limited sample size (n = 14) and reliance on a single mitochondrial marker, population-level interpretations remain preliminary. These findings demonstrate that COI barcoding is highly effective for discriminating closely related Tor species and provide important genetic baseline data for biodiversity assessment. The presence of a clear barcode gap reinforces the reliability of molecular identification, while the observed genetic patterns highlight the need for broader sampling and the application of multilocus or genomic approaches. This study contributes to conservation-oriented management by improving species resolution and supporting future efforts to delineate population structure in Indonesian freshwater ecosystems.